Detection of human cytomegalovirus genome in malignant gliomas by in situ hybridization technique - Abdullah, Shatha F.; Mukhlis, Faiza A.; Abdul majeed, Ban A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Human Cytomegalovirus ( HCMV ), lies dormant in the glial cells , and can be reactivated under conditions of inflammation and immunosuppression. In vitro, the virus can transform cells and dysregulate many cellular pathways involved in oncogenesis. This study was conducted to detect HCMV matrix-protein mRNA using In Situ Hybridization technique in glial brain tumor tissues compared to normal brain tissues and the presence of cytomegalic inclusion bodies in brain tumor tissues. Patients and Method: Thirty eight of glial tumor specimens were obtained in paraffin blocks compared to eight normal brain autopsy specimens which were age and sex matched with the study group as a control group. ISH was conducted tissue sections using a biotinylated Long DNA Probe for CMV Matrix Protein together with in-situ hybridization (ISH) detection kit. Results: The biotinylated probe specific for mRNA encoded HCMV – Matrix Protein showed hybridization with viral nucleic acids in 34 cases(out of 38)of malignant glial tumor specimens representing (73.9% ) of the total study groups . All cases with high grades astrocytoma revealed a positive hybridization in a percentage of 32.6% from 15 cases with grade III, and 10 ( 21.7% ) cases with grade IV astrocytoma. Nine out of 38 cases with grade III astrocytoma representing (23.7%), 7 (18.4 %) cases with glioblastoma multiforme and 2 oligodendroglioma cases(5.3 %), revealed inclusion bodies on histological examination. Conclusions: HCMV may play a role in the glioma pathogenesis. In Situ Hybridization test proved to be a very sensitive and specific technique for the detection of HCMV mRNA in tissues. Epidemiological, histopathological identification of cytomegalic inclusion bodies , and molecular studies are necessary to confirm the association of HCMV related human cancers in general Iraqi population.